Innovations in Practice: Body dysmorphic disorder in youth – using the Development and Well‐Being Assessment as a tool to improve detection in routine clinical practice. Issue 3 (28th February 2018) - Buckley, Vanessa; Krebs, Georgina; Bowyer, Laura; Jassi, Amita; Goodman, Robert; Clark, Bruce; Stringaris, Argyris
Abstract : Background: Body Dysmorphic Disorder (BDD) is a distressing disorder that is widely underdetected in youth. This study aimed to examine the potential utility of the Development and Well‐Being Assessment (DAWBA) as a tool to improve recognition of BDD in routine clinical practice. Methods: One hundred and sixty‐one patients assessed across two national and specialist child and adolescent mental health services, one specialising in mood disorders and one specialising in obsessive compulsive disorder and BDD, were included in this study. Results from the DAWBA were compared with clinical diagnosis to examine the utility of the DAWBA in detecting BDD. Results: Only 27% of participants who received a diagnosis of BDD at assessment had been referred with concerns about appearance anxiety suggesting significant under detection in youth mental health services. Using the single‐screener question on the DAWBA, it was possible to correctly identify 97% of cases with BDD. Conclusions: Body dysmorphic disorder often goes undetected in routine clinical practice. The DAWBA shows promise as a tool for helping clinicians to accurately detect BDD in routine clinical practice.